Canada. Significant achievements 2012 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Canada during 2012 are identified, with respect to the needs and interests of the country, strengthening issues such as food safety, plant health, animal health, trade, exports, biosafety, biotechnology, nutritional safety, small and medium-sized companies and genetically modified organisms.